Negative Interest Rates : How Big a Challenge for Large Danish and Swedish Banks? - Turk, Rima (IMF Working Papers; Working Paper ;, 2016)
Negative policy interest rates have prevailed for some years in Denmark and are a more recent development in Sweden. Among other potential side effects, negative rates could weaken banks' profitability by reducing net interest income, their main source of earnings. However, an analysis of financial statements at the country rather than the consolidated group level shows that bank margins have been broadly stable. At least to date, lower interest income was offset by reductions in wholesale funding costs and higher fee income. Nonetheless, the impacts on bank health and lending from negative interest rates will need to continue to be monitored closely.